2003
DOI: 10.1373/49.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Free p-Cresol: A Prospective and Cross-Sectional Analysis

Abstract: Background: Uremic syndrome is the consequence of the retention of solutes usually cleared by the healthy kidneys. p-Cresol can be considered a prototypic protein-bound uremic toxin. It is conceivable, analogous with drugs, that the non-protein-bound fraction of pcresol exerts toxicity. This aspect had never been evaluated, nor have the factors influencing the free fraction of p-cresol. Methods: In a transsectional study we evaluated the relationship between prehemodialysis free p-cresol and the ratio of free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 44 publications
5
88
1
Order By: Relevance
“…25 p-Cresol (acting as a surrogate for pCS) has been shown to be related to clinical outcomes. 26,27 Recent studies confirmed that free pCS levels were predictive for mortality at different stages of CKD 28 and cardiovascular and all-cause mortality in hemodialysis patients. 29 The relation between pCS and coronary artery disease in patients with no or only moderate degrees of CKD 30 extends the association of this compound with cardiovascular outcomes beyond the scope of pronounced uremia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…25 p-Cresol (acting as a surrogate for pCS) has been shown to be related to clinical outcomes. 26,27 Recent studies confirmed that free pCS levels were predictive for mortality at different stages of CKD 28 and cardiovascular and all-cause mortality in hemodialysis patients. 29 The relation between pCS and coronary artery disease in patients with no or only moderate degrees of CKD 30 extends the association of this compound with cardiovascular outcomes beyond the scope of pronounced uremia.…”
Section: Discussionmentioning
confidence: 94%
“…81 fMLP (Sigma Aldrich) dissolved in PBS at a final concentration of 4310 27 M was used as a chemoattractant; 5310 5 PMNLs were suspended in 10 ml control or an experimental solution (containing pCS, pCSpCG, or IS at the above-mentioned concentrations). After a 2-hour incubation period at 37°C, the cells were fixed with methanol and paraformaldehyde and stained with Giemsa (Merck, Darmstadt, Germany).…”
Section: Chemotaxismentioning
confidence: 99%
“…57,58 Both indoxyl sulfate and p-cresyl sulfate per se have repeatedly been related to cardiovascular mortality. [10][11][12][13][14][15][16][17][18][19] Although strategies that more efficiently remove proteinbound solutes, such as frequent dialysis 59 and online hemodiafiltration, 60,61 in controlled studies are associated with improved outcomes, 62,63 it remains difficult to interpret these data because of the presence of confounding factors that affect the outcomes on their own and a lack of selectivity of removal, because dialysis strategies are usually not restricted to protein-bound solutes alone.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In the past decade, however, a growing number of publications documented the impact of protein-bound uremic toxins on vital processes and an association of their concentration with clinical outcome parameters. 6,[10][11][12][13][14][15][16][17][18][19] One factor blurring the interpretation of the biochemical effects of uremic toxins is the application of unrealistic concentrations compared with the concentrations observed in human CKD in in vitro testing or in vivo animal experiments. 4,20 Moreover, for protein-bound toxins, even with seemingly acceptable total concentrations, the quantities of albumin or protein present are often too low, resulting in unacceptably high and thus, irrelevant free concentrations.…”
mentioning
confidence: 99%
“…In particular, studies on uremic toxicity have demonstrated that p-cresylsulfate impairs functional mechanisms only partly overlapping with those affected by p-cresol. For example, p-cresol reduces oxygen-derived free radical production by granulocytes in vitro (De Smet et al, 2003), whereas p-cresylsulfate activates free radical production by leukocytes, boosting oxidative stress (Meert et al, 2012;Schepers et al, 2007). Elevated p-cresylsulfate levels in chronic kidney disease, as well as in diabetic nephropathy, have been associated with poor clinical outcome, due to endothelial damage and vascular calcifications eventually leading to coronary heart disease (Chiu et al, 2010;Liabeuf et al, 2010;Meijers et al, 2008;Wang et al, 2010Wang et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%